2012
DOI: 10.1108/07363761211259223
|View full text |Cite
|
Sign up to set email alerts
|

Consumer behavior and purchase intention for organic food

Abstract: PurposeThe main objective of this study is to understand the behavior of ecological consumers and their intention to purchase organic food. The study aims to determine the factors influencing consumer behavior towards organic food.Design/methodology/approachThe method used for the data collection was a face‐to‐face interview, using a structured questionnaire, with closed‐ended questions. In total, 463 respondents participated in the survey. It was decided to use various multivariate analyses like multiple regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
323
1
31

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(383 citation statements)
references
References 33 publications
28
323
1
31
Order By: Relevance
“…Concern for Environment had the highest percentage of consumers, followed by concern for health. This finding coincides with the findings of Paul and Rana [35], Ahmad and Juhdi [2], Shamsollahi et al [43], Kumar and Ali [27]. 55% consumers showed less interest in certification, perhaps it could mean as a factor certification is not as important to them or they don't trust organic certification.…”
Section: Discussionsupporting
confidence: 81%
“…Concern for Environment had the highest percentage of consumers, followed by concern for health. This finding coincides with the findings of Paul and Rana [35], Ahmad and Juhdi [2], Shamsollahi et al [43], Kumar and Ali [27]. 55% consumers showed less interest in certification, perhaps it could mean as a factor certification is not as important to them or they don't trust organic certification.…”
Section: Discussionsupporting
confidence: 81%
“…Hal ini menjadi perhatian, dimana dapat diketahui daya beli konsumen. Dimana konsumen yang berada di pusat kota, memiliki daya beli lebih tinggi (Paul, 2012). Pertanyaan menarik, apakah hal ini berlaku pada keputusan konsumen dalam memiliki produk ramah lingkungan, seperti produk sayuran organik.…”
Section: Pendahuluanunclassified
“…Therefore, the information obtained from the actual purchase can help to identify the marketing strategy (Kim & Chung, 2011), customer satisfaction, and to ensure the continuity of the business (Carneiro et al, 2005;Ibrahim & Najjar, 2008;Paul & Rana, 2012). Other studies found that actual purchase is complex and vary by segment (Chiang et al, 2010;Shafiq et al, 2011).…”
Section: Actual Purchasementioning
confidence: 99%